PENGARUH FAKTOR SOSIAL, EKONOMI DAN DEMOGRAFI TERHADAP PENDAPATAN USAHA SEKTOR INFORMAL DI DESA DARMASABA - Putra, I Made Sedana; Sudibia, I Ketut (PIRAMIDA, 2018)
Various efforts can be made to increase household income, one of them through family contribution to the informal sector. The purpose of this study is to analyze the influence of education level, marital status and the number of dependents on the work hour and income in the informal sector in Darmasaba village, Badung regency. Research sample is informal sector business actors, as many as 82 respondents. Sampling was done by nonprobability sampling, accidental and snowball sampling. The analysis technique used is path analysis with hourly working hour as intervening variable. The results showed that education level, marital status and the number of dependents have a positive and significant effect on the outpouring of the working hours. The level of education, the number of dependents and the outpouring of working hours has a positive and significant impact on income. Meanwhile, marital status indicates there is no difference of income between married and unmarried status. The level of education, marital status and the number of dependents indirectly have a significant effect on income through hourly hours.